2000
DOI: 10.1109/58.818760
|View full text |Cite
|
Sign up to set email alerts
|

The experimental and theoretical characterization of the SAW propagation properties for zinc oxide films on silicon carbide

Abstract: The surface acoustic wave (SAW) propagation properties of zinc oxide (ZnO) films on silicon carbide (SiC) have been theoretically and experimentally characterized in the film thickness-to-acoustic wavelength ratio range up to 0.12. The experimental characterization of the SAW propagation properties was performed with a linear array of interdigital transducer (IDT) structures. The measurements characterized the velocity and propagation loss of two surface modes, a generalized SAW (GSAW) mode with velocities bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…11 Sorenson et al used the acoustic band gap structure as the lossless support tethers to improve the Q of AlN/Si Lamb wave resonator. 12 In addition, since silicon carbide (SiC) has a very high acoustic velocity and a low acoustic loss, 13 the AlN/SiC composite layer has been used to enhance the Q's of AlN-based resonators as well. [14][15][16] The present work demonstrates that the suspended biconvex edges can efficiently reflect the Lamb waves back towards the center of the AlN Lamb wave resonator as well as confine the displacement and the mechanical energy in the resonator.…”
mentioning
confidence: 99%
“…11 Sorenson et al used the acoustic band gap structure as the lossless support tethers to improve the Q of AlN/Si Lamb wave resonator. 12 In addition, since silicon carbide (SiC) has a very high acoustic velocity and a low acoustic loss, 13 the AlN/SiC composite layer has been used to enhance the Q's of AlN-based resonators as well. [14][15][16] The present work demonstrates that the suspended biconvex edges can efficiently reflect the Lamb waves back towards the center of the AlN Lamb wave resonator as well as confine the displacement and the mechanical energy in the resonator.…”
mentioning
confidence: 99%
“…IDTs deposition and oxide etching lower than that of the substrate, like ZnO on SiC [60]. The SAWs were generated by IDTs deposited on the ZnO layer by photolithography and metal evaporation, cf.…”
Section: Zno By Sputteringmentioning
confidence: 99%
“…by deposition of a thin film or a metal grating. The existence of this type of waves was revealed via numerical analysis of experimental data on SAW modes in ZnO/SiC structure (Didenko et al, 2000) and confirmed by other examples of layered structures, which support propagation of these waves, such as ZnO/diamond, Zno/sapphire etc. (Naumenko & Didenko, 1999).…”
Section: Zno/sapphire: Existence Of High-velocity Sawmentioning
confidence: 99%